The Impact of Risk Cycles on Business Cycles: A Historical View - Danielsson, Jon; Valenzuela, Marcela; Zer, Ilknur (Review of Financial Studies, 2023)
Abstract We investigate the effects of financial risk cycles on business cycles, using a panel spanning 73 countries since 1900. Agents use a Bayesian learning model to form their beliefs about risk. We construct a proxy of these beliefs and show that perceived low risk encourages risk-taking, augmenting growth at the cost of accumulating financial vulnerabilities, and, therefore, a reversal in growth follows. The reversal is particularly pronounced when the low-risk environment persists and credit growth is excessive. Global risk cycles have a stronger effect on growth than local risk cycles via their impact on capital flows, investment, and debt-issuer quality. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.